Effect of shrimp farming on nitrogen levels in the waters of Kandaleru creek, Andhra Pradesh - Joseph, K O; Gupta, B P; Arasu, A R T (Indian Journal of Fisheries, 2011)
Shrimp farming is a rapidly growing and economically attractive industry inmany tropical nations. In India, many shrimp farms mushroomed haphazardlyall along the coast. Production of shrimp is often limited by deterioration ofwater quality, as discharge from aquafarms ultimately reach the receiving waterssuch as rivers, creeks, estuaries and sea or land. Shrimp farms are generallydeveloped in groups and in certain locations the inlet from one farm receiveswater from the outlet of nearby farm. When compared to other industries,pollution from aquaculture is negligible and its source is the nitrogenousexcretory wastes of the cultured organisms, which may cause eutrophication inmarine/estuarine systems. A case study was undertaken in Kandaleru creekarea in Nellore District of Andhra Pradesh in order to assess the nutrient releasein terms of nitrogen, due to large scale shrimp farming and its impact onthe creek evaluated. The changes in nitrogen levels are quite high and show amarked risk of eutrophication in the creek when semi-intensive shrimp farmingis practiced in the area.